Raising Environmental Awareness: Plastic Pollution Awareness and Handling Training - Eunike, Prisca; Yuliawati, Livia; Sandjaja, Meilani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Plastic Bank Indonesia (PBI) has done trainings and evaluated its results through two modules and tests. However, it does not yet have a standardized tool to evaluate the participants’ understanding.Therefore, the purpose of this research is to evaluate the effectiveness of PBI’s trainings across two modules in order to develop a standardized tool for evaluation. This is quantitative research with a quasi-experimental design involving one experimental group without a control group and using post-test measurement only. The participants of the experinmental group are heads of warehouses and plastic collectors who received training and tests by PBI. Results show that the average score of the test falls into the category of Average and Good using an ideal norm, indicating that this training was effective in raising participants’ awareness of plastic waste. Results of the t-test show that there is no significant difference between the average scores of heads of warehouses (N=220) and plastic collectors (N=678). However, the results of the distractor test show that the majority of items are not a good distractor, which indicates that the test is still quite easy. Based on the reliability test, the majority of items have a moderate reliability (Cronbach’s alpha .5 to .7). The implication of these findings is that ineffective distractors should be revised to enhance the accuracy of evaluating participants’ understanding. Plastic Bank Indonesia (PBI) telah melakukan beberapa pelatihan dan mengevaluasi hasilnya melalui tes yang dilangsungkan dalam dua modul. Namun sejauh ini masih belum memiliki alat ukur untuk mengevaluasi pemahaman peserta pelatihan. Penelitian ini bertujuan untuk mengukur efektivitas pelatihan yang dilakukan PBI dalam modul 1 dan 2 dengan harapan agar terdapat alat ukur yang baku untuk digunakan sebagai saran evaluasi. Metode penelitian ini adalah kuantitatif dengan desain kuasi-eksperimen dengan satu kelompok eksperimen tanpa ada kelompok kontrol dengan pengukuran post-test saja. Sebanyak 898 peserta kelompok eksperimen yaitu kepala gudang dan kolektor di Indonesia yang diberikan pelatihan lalu diminta mengisi tes. Hasil rata-rata skor tes masuk dalam kategori Cukup dan Baik menggunakan normal ideal sehingga pelatihan ini efektif untuk menumbuhkan pemahaman peserta pelatihan. Hasil uji beda menunjukkan bahwa tidak ada perbedaan signifikan antara rata-rata kepala gudang (N=220) dan kolektor plastik (N=678). Namun, hasil uji distraktor menunjukkan bahwa mayoritas butir tes masih memiliki distraktor yang kurang baik yang mengindikasikan bahwa pertanyaan tes tergolong mudah. Dari hasil uji reliabilitas, mayoritas butir tes memiliki reliabilitas sedang (Cronbach’s alpha .5 sampai .7). Implikasi dari hasil ini distraktor yang kurang baik dapat direvisi untuk meningkatkan evaluasi pemahaman peserta yang lebih akurat.